Gerador rotacional piezoelétrico baseado no conceito de colheita de energia (energy harvesting) - Farias, Wendell Pereira de (2022)
This work presents a rotational generator with piezoelectric transducers of the ceramic type applied to energy harvesting, consisting of a moving part (similar to a rotor) in which magnets are arranged, and a circular structure (similar to a stator) with crimped blades equally spaced. in which piezoelectric transducers were glued close to the crimping region, and magnets at its free end. The physical structure developed, with plastic parts in ABS (Acrylonitrile Butadiene Styrene), presents flexibility regarding the number of blades, piezoelectric elements and stacking of generator modules, and keeps the piezoelectric transducers without direct contact with the external environment, allowing the adaptation of the device for practical applications. An analytical model using an electromechanical solution for a system with a cantilever beam subjected to a harmonic force at the free end was analyzed using Matlab software. The developed prototype consists of two generator modules, totaling four beams with two PZT (C-64) type piezoelectric transducers in each, and it worked for approximately 670 hours, without signs of wear. An experimental bench was developed to analyze the behavior of the proposed generator, with the generator being driven by a motor coupled to its axis with a rotation speed of 1 Hz to 35 Hz. The signals generated by the blades were connected to variable resistors, obtaining different power values in each of the blades, justified by the manual manufacturing process, a circuit was developed for interconnection and rectification of the signals, obtaining voltage and power curves as a function of the frequency of rotation, with an average power of 20 to 60 µW for resistors from 250 kΩ to 900 kΩ, where the rotation speed was set at 30 Hz. A voltage regulator module (with the LTC3588- 1) was used for energy harvesting applications that maintains the voltage supplied by the generator at 1.8 V.